Sistem Manajemen Keuangan di Madrasah Mu’alimat Muhammadiyah Yogyakarta - Feryawan, Dimas; Nabila, Zhafira An; Sambudi, Sambudi (Lembaga Yasin AlSys, 2022)
This study aims to describe how the financial management system in the Mu'alimat Muhammadiyah Yogyakarta madrasa. This research uses descriptive qualitative research method. The results of this study indicate that the financial management system at Madrasah Mu'alimat Yogyakarta uses a one-year budget plan called RAPBM (Madrasah Revenue and Expenditure Budget Plan). Financial management in Madrasah Mu'alimat is divided into two parts; The first is taking care of all incoming finances, and the second is managing the various expenses needed for the madrasa. The financial system at Madrasah Mu'aliat is evaluated at the end of every month and regularly every month. This evaluation explains the amount of budget money, expenses and income. Therefore, the management system at the Mualimat madrasa must be transparent and accountable in carrying out madrasa financial reports.